Managing surgical aphakia and posterior capsular rupture with suture-assisted intraocular lens implantation - Mukesh Kumar; Neha Chandak (Oman Journal of Ophthalmology)
OBJECTIVE This study aims to describe a novel technique for implanting an intraocular lens (IOL) in the sulcus using a 10-0 nylon suture in cases of intraoperative posterior capsular rupture (PCR) with inadequate capsular support, anterior capsular extension during continuous curvilinear capsulorrhexis extending to the posterior capsule, or posttraumatic cataract. METHODS The study included 52 patients who underwent surgery at our hospital, during which an IOL was implanted with the assistance of a 10-0 nylon suture. All patients completed a 1-year follow-up period. RESULTS In 48 of the 52 patients, the IOL remained stable. However, in two patients, the IOL dropped into the vitreous cavity approximately 1-month postsurgery. These two individuals required IOL explantation, pars plana vitrectomy, and secondary IOL (SFIOL) implantation. CONCLUSION Implanting an IOL in cases involving intraoperative PCR with inadequate capsular support, anterior capsular extension to the posterior capsule during continuous curvilinear capsulorrhexis, or posttraumatic cataract can be challenging. The technique of IOL implantation with the assistance of a 10-0 nylon suture, as described in this study, offers a straightforward and safe approach. In addition, it can help alleviate the financial and psychological trauma associated with a second surgery for both the patient and the surgeon.